MEDIATION FOR INDONESIAN TAX DISPUTES: IS IT POTENTIAL ALTERNATIVE STRATEGY FOR RESOLVING INDONESIAN TAX DISPUTES? - Hidayah, Khoirul; Suhariningsih, Suhariningsih; Istislam, Istislam (Indonesia Law Review, 2018)
Tax dispute resolution in Indonesia has not yet met the principles of quick, simple, and economical. Taxpayers have to wait more than 3 years for the lawful certainty. This paper elaborates the potential strategy in resolving the tax dispute in Indonesia through administrative law. OECD has suggested taxpayers and revenue body to build positive connection through the changing of confrontation to the collaborative relationship. Mediation is a solution to encourage this positive bond in solving the dispute. It is successfully implemented in Australia. The similar way is strongly recommended for the Indonesian Government to develop a good relationship between taxpayers and revenue body. One of the chances for mediating in an attempt to minimize tax dispute is in the auditing process. This process cannot be easily done because it needs political will and high desired improvement from the Government to make a change. Mediation is an attempt to achieve a win-win solution and is in line with the principles of Pancasila, that is a deliberation for reaching an agreement. If it is done, then mediation will be a courteous way in tax dispute resolution and will be able to improve a good post-dispute relationship in Indonesia.